1998
DOI: 10.1111/j.1472-8206.1998.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptors involved in the positive inotropic action induced by dopamine on the ventricle of a 7‐day‐old chick embryo heart

Abstract: Earlier experiments only revealed involvement of sympathetic pre-synaptic dopaminergic receptors in dopamine induced inotropism in myocardium. We therefore used electrically stimulated (1 Hz) isolated 7-day-old chick embryo heart ventricles, thought to be devoid of functional sympathetic nerves, to re-investigate post-synaptic receptors involvement and particularly that of dopaminergic receptors in the positive inotropic effect of dopamine. The results showed that noradrenaline, isoprenaline and dopamine produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
3
1
Order By: Relevance
“…The highest pD) 2 value and the lowest slope and E max were reported for haloperidol combined with dopamine. Accordingly, it could be suggested that interaction of haloperidol with dopamine at dopamine D 2 receptors is implicated in the negative inotropic effect of haloperidol [38]. However, our results showed that the pattern of interference of dopamine with haloperidol was of a noncompetitive pattern.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The highest pD) 2 value and the lowest slope and E max were reported for haloperidol combined with dopamine. Accordingly, it could be suggested that interaction of haloperidol with dopamine at dopamine D 2 receptors is implicated in the negative inotropic effect of haloperidol [38]. However, our results showed that the pattern of interference of dopamine with haloperidol was of a noncompetitive pattern.…”
Section: Discussioncontrasting
confidence: 69%
“…The dopamine D 2 receptors are involved in the direct positive inotropic effect of dopamine, as dopamine increases [Ca 2+ ] i through actions mediated by dopamine D 2 receptors [37]. Moreover, it has been reported that haloperidol reduces the inotropic effect of dopamine [36,38] and of dopaminergic drugs [39]. In this study, dopamine diminished the negative inotropic effect of haloperidol.…”
Section: Discussionsupporting
confidence: 52%
“…Whether these early appearing receptors are functional is not known. Chick myocytes were responsive to catecholamines at E7 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Whether these early appearing receptors are functional is not known. Chick myocytes were responsive to catecholamines at E7 [34]. When E15 chick embryos were challenged with the inotropic hormones isoproterenol or dopamine, [ 125 I]Mel binding densities in the heart increased, indicating that they can be regulated at E15.…”
Section: Discussionmentioning
confidence: 99%
“…6B). The receptors producing the direct inotropic effects of DA in the heart were reported for rabbit [30,31] and man [32] to be β-and α-adrenoceptors, for guinea pig [9] and rat [33] to be β-adrenoceptor only, and for chick embryo [34] to be β-adrenoceptor and subtype DA2-receptors. DA has been shown to increase L-type Ca 2+ currents and to produce the inotropic effect that is mediated through the direct stimulation of β-adrenoceptor in the single atrial and ventricular myocytes of the rat [33].…”
Section: Dosementioning
confidence: 99%